Quality Assurance In The Age Of Personalized Medicine: Challenges And Opportunities - Sanjay Pathak, Swanand; Gawai, Ashish; Biyani, K.R (Asian Journal of Pharmaceutical Research and Development, 2024)
The abstract of the document "Quality Assurance in the Age of Personalized Medicine" provides an overview of the challenges and opportunities presented by personalized medicine in the healthcare landscape. It discusses how the individualized nature of personalized therapies, coupled with regulatory complexities and data management issues, complicates the development, approval, and commercialization of personalized treatments. Despite these challenges, the abstract highlights the potential for innovation and advancement in quality assurance through the use of emerging technologies like artificial intelligence, machine learning, and big data analytics. These technologies can enhance diagnostic test predictability, optimize treatment selection algorithms, and improve patient stratification strategies. Furthermore, the abstract emphasizes the shift towards patient-centered care and shared decision-making, empowering patients to actively participate in their treatment journeys and fostering collaboration between patients, providers, and industry stakeholders. Overall, the abstract sets the stage for exploring the complexities and opportunities in quality assurance within the realm of personalized medicine.